Cardiac Magnetic Resonance Studies in a Large Animal Model That Simulates the Cardiac Abnormalities of Human Septic Shock - Verity J. Ford; Willard N. Applefeld; Jeffrey Wang; Junfeng Sun; Steven B. Solomon; Stanislav Sidenko; Jing Feng; Cynthia Sheffield; Harvey G. Klein; Zu‐Xi Yu; Parizad Torabi‐Parizi; Robert L. Danner; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Septic shock is associated with increases in end‐diastolic volume (EDV) and decreases in ejection fraction that reverse within 10 days. Nonsurvivors do not develop EDV increases. The mechanism is unknown. Methods and Results Purpose‐bred beagles (n=33) were randomized to receive intrabronchial Staphylococcus aureus or saline. Over 96 hours, cardiac magnetic resonance imaging and echocardiograms were performed. Tissue was obtained at 66 hours. From 0 to 96 hours after bacterial challenge, septic animals versus controls had significantly increased left ventricular wall edema (6%) and wall thinning with loss of mass (15%). On histology, the major finding was nonocclusive microvascular injury with edema in myocytes, the interstitium, and endothelial cells. Edema was associated with significant worsening of biventricular ejection fractions, ventricular‐arterial coupling, and circumferential strain. Early during sepsis, (0–24 hours), the EDV decreased; significantly more in nonsurvivors (ie, greater diastolic dysfunction). From 24 to 48 hours, septic animals' biventricular chamber sizes increased; in survivors significantly greater than baseline and nonsurvivors, whose EDVs were not different from baseline. Preload, afterload, or heart rate differences did not explain these differential changes. Conclusions The cardiac dysfunction of sepsis is associated with wall edema. In nonsurvivors, at 0 to 24 hours, sepsis induces a more severe diastolic dysfunction, further decreasing chamber size. The loss of left ventricular mass with wall thinning in septic survivors may, in part, explain the EDV increases from 24 to 48 hours because of a potentially reparative process removing damaged wall tissue. Septic cardiomyopathy is most consistent with a nonocclusive microvascular injury resulting in edema causing reversible systolic and diastolic dysfunction with more severe diastolic dysfunction being associated with a decreased EDV and death.